(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article explores the importance of preparing girls for family life by instilling national values. It discusses the methods, results, and implications of aligning education and parenting practices with cultural and traditional values. The article emphasizes the need for a balanced approach that empowers girls to embrace their roles in the family while promoting gender equality and individual growth.